Balancing Selection on a Single Locus Controls Colour Polymorphism in a Reptile via Tubulin Modification - Hongxin Xie; Danyang Wu; Guannan Wen; Xixi Liang; Shuyi Luo; Chunsheng Yang; Kathryn R. Elmer; Weiguo Du (Molecular Ecology, 2026)
Animal coloration, a key morphological trait for communication, offers a powerful model for studying the evolution of discrete phenotypes. Reptiles display a striking diversity in skin coloration, yet the mechanisms underlying these traits remain poorly characterised. Here we investigated the genetic and molecular basis of red pigmentation in the endangered Chinese crocodile lizard ( Shinisaurus crocodilurus ). We showed that while the distinct red crossbands are present as a discrete polymorphism in both sexes, they are associated with individual quality in males but not in females. Red males exhibit better body condition and larger heads. By constructing a haplotype‐resolved, chromosome‐level genome, we combined population genomics and captive breeding data to map the trait to a single dominant autosomal locus. This locus shows evidence of variation being maintained by strong balancing selection, illustrating how a simple genetic switch can sustain phenotypic diversity. We identified tubulin polyglutamylase TTLL6 , a gene with fixed coding mutations between red and non‐red haplotypes, as the prime candidate. The two variants of the gene encode structurally different proteins that may differ in their catalytic function. Our mechanistic modelling of intracellular pigment granule trafficking demonstrates that, in principle, a modification in tubulin tail polyglutamylation can determine pigment deposition. Histology further revealed that red skin regions are characterised by pigment‐dispersed chromatophores. These results suggest that TTLL6 may have been selected for the red crossband polymorphism, likely by regulating microtubule‐based pigment granule trafficking. Our findings implicate microtubule‐mediated mechanisms as a novel pathway underlying reptile colour polymorphism.